Decision support system for analyzing the level of satisfaction of library services using the analytic hierarchy process method - Agus Kurniawan, Rafiq; Khairil, Khairil; Zulfiandry, Ricky (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
The utilization of Decision Support Systems can help humans decide things quickly, accurately and consistently. Dehasen University Library has difficulty in considering library services that need to be improved. The research method used in this research is the waterfall model method carried out is a needs analysis, namely determining needs, system design from needs analysis, making programs to design by writing program code, program implementation and testing of the system created. This decision support system is made using the native php programming language so as to speed up the determination of landfills by implementing the moora method. This SPK is also integrated into the MySQL database. From the results of research with this system more accelerate the selection ranking with several alternatives, and testing done with the manual process there is no difference.